2013
DOI: 10.1590/s1984-82502013000100014
|View full text |Cite
|
Sign up to set email alerts
|

2-Phenitidine derivatives as suitable inhibitors of butyrylcholinesterase

Abstract: This manuscript reports the synthesis of a series of N-substituted derivatives of 2-phenitidine. First, the reaction of 2-phenitidine (1) with benzene sulfonyl chloride (2) yielded N-(2-ethoxyphenyl) benzenesulfonamide (3), which further on treatment with sodium hydride and alkyl halides (4a-g) furnished into new sulfonamides (5a-g). Second, the phenitidine reacted with benzoyl chloride (6) and acetyl chloride (8) to yield the reported N-benzoyl phenitidine (7) and N-acetyl phenitidine (9), respectively. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…16 Different microbes have been found to be involved in many diseases [17][18][19][20][21][22] and some of them are included in the current study. So, in continuation of our previous work on carbamates, [23][24][25] hereby we report the synthesis of some unique carbamates having amalgamation with 2-furoylpiperazine moiety, which might find their utility as potential and safe thereapeutic agents.…”
Section: Introductionmentioning
confidence: 73%
“…16 Different microbes have been found to be involved in many diseases [17][18][19][20][21][22] and some of them are included in the current study. So, in continuation of our previous work on carbamates, [23][24][25] hereby we report the synthesis of some unique carbamates having amalgamation with 2-furoylpiperazine moiety, which might find their utility as potential and safe thereapeutic agents.…”
Section: Introductionmentioning
confidence: 73%
“…The compounds bearing sulfamoyl moiety have previously been synthesized by our group [12,13] and their biological activities have been shown to be related to structural modification in the molecules. The overview of compounds showing activity against both enzymes revealed that molecules bearing small N-substitution like propyl group were better inhibitors because of best fit to active site of enzyme.…”
Section: N-(naphthalen-1-yl)-4-acetamidobenzenesulfonamide (3)mentioning
confidence: 99%
“…In continuation of our previous work in this regard [12][13][14], new sulfonamides derived from dagenan chloride have been synthesized in order to assess their enzyme inhibition activities.…”
Section: Introductionmentioning
confidence: 99%
“…In continuation of our previous efforts for the search of cholinesterase inhibitors [11][12][13], here we report the synthesis of some new 4-{[4-(2-furoyl)-1-piperazinyl]methyl}-N-(substituted-phenyl) benzamides as valuable therapeutic agents aiming to play a pivitol role in the treatment of Alzheimer's disease.…”
Section: Introductionmentioning
confidence: 99%